2013
DOI: 10.2147/opth.s46792
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-resistant Staphylococcus hominis endophthalmitis following cataract surgery

Abstract: We report a case of acute postoperative endophthalmitis caused by vancomycin-resistant Staphylococcus hominis, treated at our hospital. An 80-year-old male presented 2 days after uncomplicated phacoemulsification and posterior chamber intraocular lens implantation, with a 24-hour history of progressive visual loss and redness in the operated (right) eye. On examination, best corrected visual acuity was counting fingers. Anterior segment examination revealed conjunctival injection, chemosis, corneal edema, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…hominis infections, particularly those resistant to vancomycin and linezolid and those carrying the SCC mec gene. [ 10 , 37 ] Recent phenotypic and molecular characterisations of S . hominis clinical isolates have found that S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hominis infections, particularly those resistant to vancomycin and linezolid and those carrying the SCC mec gene. [ 10 , 37 ] Recent phenotypic and molecular characterisations of S . hominis clinical isolates have found that S .…”
Section: Discussionmentioning
confidence: 99%
“…hominis infections are often highly resistant to antibiotics and thus, are difficult to treat. Resistance to linezolid and vancomycin has been reported in several isolates [ 8 10 ]. Furthermore, methicillin resistance, which is associated with the mecA gene, has been found in up to 80% S .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the emergence of vancomycin-resistant staphylococci, a reduction in the use of this antibiotic has been recommended. Recently, Won and Kim ( 2013 ) has reported the emergence of vancomycin-resistant S. hominis. Also, the emergence of resistance to relatively new antibiotics, such as linezolid and quinupristin/dalfopristin, has also been noted, in clinical S. hominis strains (Petinaki et al 2005 ; Ruiz de Gopegui et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…hominis in certain conditions have been reported to possess vancomycin resistance gene Won and Kim. 28 Hence, it is of relevance to highlight the sensitivity of the isolates to vancomycin. Based on this finding, vancomycin can be an effective agent in the management of LF-related wound infections.…”
Section: Discussionmentioning
confidence: 99%